ANALISIS PENGARUH KINERJA LINGKUNGAN, MANAJEMEN LABA, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN LINGKUNGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Julianto, Melvin; Sjarief, Julianti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2016)
The purpose of this study is to analyze the effect of environmental performance, earnings management, firm size, and profitability to environmental disclosure. This study uses descriptive analysis and multiple linear regression analysis to examine the relationship between independent and dependent variable on 42 manufacuture companies listed in Indonesia Stock Exchange period 2011-2013. Environmental performance is measured using PROPER; earnings management is measured using discretionary accrual model Kothari et al. (2005); firm size measured using Log10 of total assets; profitability is measured using ratio of profit margin; environmental disclosure measured using  Patten (2002) environmental disclosure item. This study found that environmental performance and firm size have impact on environmental disclosure. However earnings management and profitability have no impact on environmental disclosure.